Memoryscapes: Southeast Europe and the Question of “Small/Minor” Literature - Gorica Majstorovic (Acta Universitatis Carolinae Studia Territorialia, 2021)
Drawing on recent discussions in world literature and Michael Rothberg’s concept of multidirectional memory, in the present article I explore Danilo Kiš and Dubravka Ugrešić within the formation of transactional exchanges between “small/minor” and world literatures. As I approach these exchanges, my focus is on texts and contexts in which translation and memory function as the key mediator. By reading Kiš and Ugrešić comparatively, my aim, in what I call “the minor drive,” is to address writers and translators that contest hegemonic narratives, and in doing so, examine the cultural enterprise of “small/minor” literatures from the perspective of “worlding” former Yugoslavia and Southeast Europe.